Expansion of Host Regulatory T Cells by Secreted Products of the Tapeworm Echinococcus multilocularis - Nono, Justin Komguep; Lutz, Manfred B.; Brehm, Klaus (Frontiers in Immunology, 2020)
Background: Alveolar echinococcosis (AE), caused by the metacestode larval stage of the fox-tapeworm Echinococcus multilocularis, is a chronic zoonosis associated with significant modulation of the host immune response. A role of regulatory T-cells (Treg) in generating an immunosuppressive environment around the metacestode during chronic disease has been reported, but the molecular mechanisms of Treg induction by E. multilocularis, particularly parasite immunoregulatory factors involved, remain elusive so far. Methodology/Principal findings: We herein demonstrate that excretory/secretory (E/S) products of the E. multilocularis metacestode promote the formation of Foxp3+ Treg from CD4+ T-cells in vitro in a TGF-b-dependent manner, given that this effect was abrogated by treatment with antibody to mammalian TGF-b. We also show that host T-cells secrete elevated levels of the immunosuppressive cytokine IL-10 in response to metacestode E/S products. Within the E/S fraction of the metacestode we identified an E. multilocularis activin A homolog (EmACT) that displays significant similarities to mammalian Transforming Growth Factor-b (TGF-b/activin subfamily members. EmACT obtained from heterologous expression failed to directly induce Treg expansion from naïve T cells but required addition of recombinant host TGF-b to promote CD4+ Foxp3+ Treg conversion in vitro. Furthermore, like in the case of metacestode E/S products, EmACT-treated CD4+ T-cells secreted higher levels of IL-10. These observations suggest a contribution of EmACT to in vitro expansion of Foxp3+ Treg by the E. multilocularis metacestode. Using infection experiments we show that intraperitoneally injected metacestode tissue expands host Foxp3+ Treg, confirming the expansion of this cell type in vivo during parasite establishment. Conclusions/Significance: In conclusion, we herein demonstrate that E. multilocularis larvae secrete factors that induce the secretion of IL-10 by T-cells and contribute to the expansion of TGF-b-driven Foxp3+ Treg, a cell type that has been reported crucial for generating a tolerogenic environment to support parasite establishment and proliferation. Among the E/S factors of the parasite we identified a factor with structural and functional homologies to mammalian activin A which might play an important role in these activities.